Determinants of Sustainable Growth Rate in Digital Start-up Companies in Indonesia - Nasrullah; Muhammad Nur Abdi; Mushawir (www.amertainstitute.com, 2024)
The Sustainable Growth Rate (SGR) is a key concept in financial management, indicating the maximum growth rate a company can achieve without relying on additional external financing. This study aims to analyze the factors influencing SGR, focusing on leverage, asset turnover, profitability, and liquidity. Data were obtained from the financial and annual reports of 10 companies for the period 2021–2023, sourced from the Indonesia Stock Exchange’s official website (idx.co.id) and the respective websites of each company.The data analysis was conducted using Eviews 13, applying panel data regression in a quantitative approach. The results revealed that leverage, as measured by the debt-to-asset ratio (DAR), and profitability, as measured by return on assets (ROA), significantly impacted the Sustainable Growth Rate (SGR), with a significance level of P < 0.05. However, asset turnover, proxied by the total asset turnover ratio (TATO), and liquidity, proxied by the current ratio (CR), did not show a significant effect on SGR, with P > 0.05.These findings suggest that higher leverage and profitability levels contribute positively to a company’s sustainable growth potential, while asset turnover and liquidity do not significantly influence the SGR. Consequently, companies aiming to achieve optimal growth may focus on maintaining favorable leverage and profitability levels without placing undue emphasis on asset turnover or liquidity ratios. This research offers insights into how companies listed on the Indonesia Stock Exchange can manage internal financial factors to support sustainable growth.